Progressive Steps of Polymorphic Transformation of Gabapentin Polymorphs Studied by Hot-stage FTIR Microspectroscopy - Cheng-Hung Hsu; Wen-Ting Ke; Shan-Yang Lin (Frontiers Media S.A., 2010)
Purpose. The aim of this study was to determine the progressive processes of polymorphic transformation of different gabapentin (GBP) polymorphs by using hot-stage Fourier transform infrared (FTIR) microspectroscopy. Methods. Four polymorphs of GBP were previously prepared and then identified by differential scanning calorimetry (DSC), thermogravimetric (TG) analysis, FTIR microspectroscopy and X-ray powder diffractometry. A novel hot-stage FTIR microspectroscopic technique was used to investigate the progressive steps of polymorphic transformation of each GBP polymorph sealed within two pieces of KBr plates. Results. Four polymorphs (Forms I, II, III and IV) of GBP were well characterized. The GBP form I was proven to be a monohydrate, but other GBP forms II-IV were anhydrous. Different thermal-induced progressive processes and steps of polymorphic interconversion of GBP polymorphs were clearly found from the changes in the three-dimensional IR spectral contour and peak intensity by using hot-stage FTIR microspectroscopy. The results also indicate that GBP form I was dehydrated and transformed to form III, and then converted to form IV; whereas GBP forms II and III directly transformed to form IV during heating. The GBP form IV was the last polymorph before the intramolecular lactamization of GBP. Conclusion. A one-step novel hot-stage FTIR microspectroscopy was successfully applied to simultaneously and continuously investigate the progressive processes and steps of thermal-induced polymorphic interconversion of GBP polymorph in the solid state.